The Legacy of Sickness Behaviors - Keith W. Kelley; Keith W. Kelley; Keith W. Kelley; Stephen Kent; Stephen Kent (Frontiers in Psychiatry, 2020)
Systemic infections of all types lead to a syndrome known as sickness behaviors. Changes in the behavior of febrile humans and animals formed the original basis for this concept. Body temperature is behaviorally regulated in both endotherms and ectotherms. However, infections cause other changes in body functions, including sleep disruption, anorexia, cognitive and memory deficits and disorientation. The brain mediates this entire cluster of symptoms, even though most major infections occur outside the brain. The true importance of sickness behaviors is not the numerous discoveries of symptoms that affect all of us when we get sick. Instead, the legacy of 30 years of research in sickness behaviors is that it established the physiologic importance of reciprocal communication systems between the immune system and the brain. This conceptual advance remains in its infancy.